Fundamentals of natural gas : an international perspective - Chandra, Vivek (PennWell Corp., 2006)
"Natural Gas has been called "the prince of hydrocarbons," an abundant resource that is versatile, competitive with other fuels and popular throughout the world. Newer technologies that can deliver natural gas to worldwide markets coupled with its reputation as a clean-building, efficent energy source make natural gas the international "fuel of the future." Key features and Benefits are: --Thorough understanding of the entire natural gas value chain --Gas terms, conversion units, commercialization, and marketing issues --Current and emerging international players, and the latest in techology development."
Keywords: Natural gas.; elektronické knihy; electronic books